2009
DOI: 10.1186/1471-2407-9-367
|View full text |Cite
|
Sign up to set email alerts
|

Predicting for activity of second-line trastuzumab-based therapy in her2-positive advanced breast cancer

Abstract: BackgroundIn Her2-positive advanced breast cancer, the upfront use of trastuzumab is well established. Upon progression on first-line therapy, patients may be switched to lapatinib. Others however remain candidates for continued antibody treatment (treatment beyond progression). Here, we aimed to identify factors predicting for activity of second-line trastuzumab-based therapy.MethodsNinety-seven patients treated with > 1 line of trastuzumab-containing therapy were available for this analysis. Her2-status was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Our results, which are similar to other retrospective studies, indicate that durable disease control can be achieved with repeated or prolonged exposure to trastuzumab. The median TTP of 6 months with second-line treatment in our study is consistent with reports in the literature [21,22] . The predominant chemotherapy partners in the second-line setting were vinorelbine and taxane, as in the first-line setting.…”
Section: Discussionsupporting
confidence: 82%
“…Our results, which are similar to other retrospective studies, indicate that durable disease control can be achieved with repeated or prolonged exposure to trastuzumab. The median TTP of 6 months with second-line treatment in our study is consistent with reports in the literature [21,22] . The predominant chemotherapy partners in the second-line setting were vinorelbine and taxane, as in the first-line setting.…”
Section: Discussionsupporting
confidence: 82%
“…An increase in the incidence of BM was observed in recent years, which is usually attributed to the introduction of trastuzumab-based therapy ( Bendell et al , 2003 ; Clayton et al , 2004 ; Shmueli et al , 2004 ; Burstein et al , 2005 ; Viani et al , 2007 ). Recently, it was reported that up to 40% of all HER2-positive metastatic breast cancer patients will be eventually diagnosed with BM ( Bartsch et al , 2009 ). Other studies, however, suggest that even in the absence of trastuzumab, women with HER2-positive metastatic breast cancer are at increased risk for BM as compared with women with HER2-negative disease ( Pestalozzi and Brignoli, 2000 ; Pestalozzi et al , 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of resistance to trastuzumab is still not fully understood. Consequently, the identification of clinical or histopathologic factors to define a population gaining benefit from trastuzumab continuation was unsuccessful so far . Only few possible immunologic characteristics such as immunoglobulin G Fragment C receptor polymorphisms were identified to predict for activity of trastuzumab in the induction of antibody‐dependent cytotoxicity .…”
Section: Discussionmentioning
confidence: 99%